Einstein's Philosophy Politely Shelved*. (July 2015) - Agassi, Joseph
Einstein considered fallibilist methodology obvious and metaphysics the challenging heuristic of physics. This philosophy is a minority view in academic philosophy. Most commentators on Einstein reject it and either refuse to ascribe it to him or declare it an impediment to his researches, his own opinion to the contrary notwithstanding.